Nurses Perspectives Causes And Management Strategies To Prevent Medication Errors: Qualitative Study - Martha Sasmita Ningrum; Jovita Irawati (Penerbit Goodwood, 2025)
Purpose: This study aims to explore the causes of medication errors, prevention strategies, and the role of hospital management in reducing such errors, based on the perceptions of nurses. Methodology/approach: This qualitative research used a thematic analysis approach and was conducted at a private hospital in Surabaya. Data were collected through in-depth interviews with 10 informants—7 shift-leading nurses and 3 head nurses—who met the inclusion criteria. MAXQDA Pro 2024 was used for data coding and analysis. The analysis process included transcription, initial coding, theme development, and interpretation based on Lincoln and Guba’s trustworthiness criteria. Results/findings:The main causes of medication error were identified as lack of double-checking, crowded work environments, poor documentation, communication issues, and limited experience. Prevention strategies included implementation of double-check procedures, communication improvement, regular training, and integration of technology. Management roles such as supervision, SOP revision, and Root Cause Analysis (RCA) were essential in supporting safe medication practices. Conclusions: Management's role is considered crucial in establishing a system that supports patient safety through policies such as supervision, training, SOP revisions, and conducting Root Cause Analysis (RCA) for any unforeseen incidents, thereby ensuring that the implemented nursing management strategies become more effective and efficient. Limitations: This study is limited to one hospital with a small number of participants and does not include perspectives from other healthcare professionals like pharmacists or physicians. Contribution: The study contributes to patient safety literature and provides actionable insights for hospital administrators, nurse managers, and healthcare policymakers to improve medication safety.